PELATIHAN MUSIK BALEGANJUR UNTUK MENINGKATKAN KETERAMPILAN BERMUSIK GENERASI MUDA DI PURA BUANA AGUNG BONTANG: Baleganjur Music Training to Improve the Musical Skills of the Young Generation at Buana Agung Bontang Temple - Yofi Irvan Vivian; Putra, Agus Kastama; Yohana, Saferi (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2024)
Abstract: The baleganjur music training at Pura Buana Agung, Bontang, aims to improve the musical skills of the young generation of Balinese Hindus. This temple is the center of religious and cultural activities for the Hindu community living in Bontang. This activity was attended by 16 teenagers who were actively involved in the baleganjur ensemble training, which is a sacred form of traditional Balinese music. The training method included a pre-test to measure participants' initial knowledge, an interactive material session, and a post-test to assess increased understanding. The evaluation results showed a significant increase in participants' knowledge of baleganjur, with post-test scores higher than pre-test scores. This training not only develops musical skills, but also instills the values ​​of togetherness and discipline, in line with the principles of Balinese Hindu life. This activity contributes to strengthening cultural identity and supporting the preservation of traditional music amidst migration and social change. Thus, the existence of Pura Buana Agung has an important role in maintaining and advancing the richness of Balinese Hindu culture in Bontang, as well as connecting past and future generations.  Keywords: baleganjur music; skill improvement; young generation.   Abstrak: Pelatihan musik baleganjur di Pura Buana Agung, Bontang, bertujuan untuk meningkatkan keterampilan bermusik generasi muda Hindu Bali. Pura ini menjadi pusat kegiatan keagamaan dan budaya bagi komunitas Hindu yang tinggal di Bontang. Kegiatan ini dihadiri oleh 16 remaja yang terlibat aktif dalam pelatihan ansambel baleganjur, yang merupakan bentuk musik tradisional Bali yang sakral. Metode pelatihan meliputi pre-test untuk mengukur pengetahuan awal peserta, sesi materi interaktif, dan post-test untuk menilai peningkatan pemahaman. Hasil evaluasi menunjukkan peningkatan signifikan dalam pengetahuan peserta tentang baleganjur, dengan nilai post-test yang lebih tinggi dibandingkan pre-test. Pelatihan ini tidak hanya mengembangkan keterampilan musik, tetapi juga menanamkan nilai-nilai kebersamaan dan disiplin, sejalan dengan prinsip kehidupan umat Hindu Bali. Kegiatan ini berkontribusi pada penguatan identitas budaya dan mendukung pelestarian musik tradisional di tengah migrasi dan perubahan sosial. Dengan demikian, keberadaan Pura Buana Agung memiliki peran penting dalam mempertahankan dan memajukan kekayaan budaya Hindu Bali di Bontang, serta menghubungkan generasi masa lalu dan masa depan. Kata kunci: musik baleganjur; peningkatan keterampilan; generasi muda.